Self-Esteem in the Qur’an: Meaning and Contextual Relevance in the Contemporary Era - Fatekhah, Rully; Zaini Dahlan (Journal of Ushuluddin and Islamic Thought, 2023)
The concept of self-esteem is a fundamental aspect in the formation of a dignified human civilization, as reflected in the teachings of the Qur’an. Amidst the growing identity crisis and existential challenges of modern humans, the study of the Qur’an’s understanding of self-esteem has become increasingly relevant. This study aims to examine the concept of self-esteem in the Qur’an and explore its contextualization and relevance in a contemporary context. This study uses a qualitative method with a descriptive and analytical approach, and refers to Abdullah Saeed’s contextual theoretical framework to understand the text in its historical and contemporary contexts. The results of the study indicate that verses such as Surah al-Isrā’ [17]: 62 and 70, Surah al-Furqān [25]: 72, and Surah al-Ḥujurāt [49]: 13 affirm the uniqueness of humans as beings endowed with reason, honor, and moral potential. These values align with modern psychological principles regarding the importance of self-esteem in shaping character and integrity. This study affirms that strengthening self-esteem through a holistic understanding of Islam has the potential to make an important contribution to the development of human resources and the formation of an inclusive and civilized society.